Experimental Investigation on Electrical and Physicochemical Properties of POME-Based TiO2-ZnO HNF Under Transesterification Process and Thermal Ageing - Ernieza, Musa (UNIMAS Institutional Repository (IR), 2025)
Mineral-based oil is a staple in the transformer industry due to its outstanding dielectric properties as an insulation system and its ability to allow electrical power network operation. The transition towards a more sustainable insulating oil in transformers instead of traditional mineral-based oil has been the subject of study for many years. Alternatives to a biodegradable resource, particularly palm oil, have been explored due to its abundance and properties that can mimic those of mineral-based oil. Recent developments have shown improvements in electrical insulation by combining palm oil's benefits and nanoparticles, known as monotype nanofluid (MNF). While ongoing studies on MNFs have yielded major findings, the investigation of hybrid nanofluid (HNF) has not yet become common. This research focuses on the production of POME-based HNFs, which involves three-phase experimental procedures (POME preparation using transesterification, HNF preparation using a two-step method involving TiO2 and ZnO NPs with concentrations of 0.05 g/L, 0.10 g/L, 0.15 g/L, and 0.20 g/L, and accelerated thermal ageing at 135 ℃ at 0-hr, 50-hrs, 500-hrs, and 1000-hrs). Compared to other concentrations, 0.05 g/L of TiO2-ZnO HNF showed the steadiest increase for AC BDV from 26.8 to 61.4 kV as the ageing time increased, as well as an increment from 36.4 to 290.8 %. The densities and viscosities of the POME-based TiO2-ZnO HNFs fall in the acceptable range of 0.86 to 0.89 g/cm3 and 6.86 to 8.00 cSt at 40 ℃, as per ASTM D7777 and ASTM D445, respectively. Based on FTIR spectroscopy, the molecular structure and chemical bonding of the pure POME and POME-based TiO2ZnO HNFs and UV-Vis spectroscopy on the variation concentrations on the stability of TiO2-ZnO HNFs did not significant change. These results provide insight into the performance of TiO2-ZnO HNFs as insulation in an actual transformer.